2019
DOI: 10.1016/j.jad.2018.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Negative peer social interactions and oxytocin levels linked to suicidal ideation in anxious youth

Abstract: Background-Anxious youth are at risk for negative peer interactions including peer victimization, and for suicidal ideation. However, data about the pattern of association between these two factors are scarce. In this study we examined the association between negative peer interactions and suicidal ideation in a sample of children and adolescents with anxiety disorders, and whether oxytocin, which has been shown to enhance the impact of social events, moderates the impact of negative peer interactions on suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…In addition, a generation of new methods to identify other currently implicated and novel molecular mechanisms is needed. For example, a link between oxytocin and SI was recently suggested [208].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a generation of new methods to identify other currently implicated and novel molecular mechanisms is needed. For example, a link between oxytocin and SI was recently suggested [208].…”
Section: Future Directionsmentioning
confidence: 99%
“…Future studies should also further investigate the more elusive subjective aspects of suicide risk, such as SI, as well as implicated psychological constructs such as hopelessness, rumination, and anhedonia [209][210][211], which may be relevant across diagnoses. Similarly, social experiences such as childhood maltreatment and peer bullying form a strong prelude to STB in later life [208,212,213], and impact on the neural structures implicated in STB (e.g., DMPFC structure and function [214,215]). Therefore, adverse experiences should be taken into account in future studies on the neurobiology of STB.…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies could also investigate more aspects of suicidal risks, such as hopelessness and rumination (Miranda and Nolen-Hoeksema, 2007). Furthermore, there is a consensus indicating that childhood trauma may be related to the development of depression (Negele et al, 2015); moreover, childhood abuse and peer bullying could form a prelude to suicidal ideation or behaviors in the future (Peyre et al, 2017;Lebowitz et al, 2019). Therefore, social experiences should also be investigated in future studies since advanced interventions for psychiatric disorders may reduce the burden of suicide and may be helpful for clinical diagnoses.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Later, the same authors showed that carriers of the A allele of rs3796863 were more sensitive to unsupportive social interactions with their peers (relationships that bring pain, suffering, sadness, isolation, rejection, and troubles) [40]. Lebowitz et al found that the influence of negative relationships with peers more often led to suicidal ideations in adolescents with high levels of OT in saliva, which also supports the hypoth esis of OT-mediated excessive social sensitivity [53].…”
Section: Discussionmentioning
confidence: 93%